Metafora snu w cyklu wierszy Inny Lisnianskiej Sny starej Ewy - Nikadem-Malinowska, Ewa (Acta Polono-Ruthenica, 2008)
Inna Lisnianskaya’s writings, very private and intimate, often motivated with autobiographical reasons is saturated with universal truth about life. Lisnianskaya has created her poetic world on the basis of very strict and clear hierarchy of values. All of the problems of the mankind the poetess throw on her character who, with a great conscientiousness, carries her burden. The global responsibility she feels makes the linear world stop existing.In consisting of eighteen poems threnody series Inna Lisnianskaya experiences past and future in the presence by impersonating her character - ageing biblical Eve. The presence constitutes of her dreams. Dream is metaphorical by its nature. We do not treat pictures from our dreams literally. We analyze and interpret them no matter how real they are. A specific picture transferred from reality to a dream loses its connections with its context and become a polysemantic sign of another specific picture. In this way a dream manifests its metaphorical character.Metaphorical picture of a dream dreamt by lyrical I, created by Inna Lisnianskaya in the series of poems Сны старой Евы (Dreams o f Old Eve), let the poetess for unique consolidation of emotions and reflections on life and death.